2021
DOI: 10.3390/jcm10081678
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Safety Assessment of Autologous Freeze-Drying Platelet-Rich Plasma for Bone Regeneration in Maxillary Sinus Floor Augmentation: A Pilot Study

Abstract: The purpose of this clinical study is to evaluate the safety and preliminary efficacy of autologous freeze-drying platelet-rich plasma (FD-PRP) on bone regeneration in maxillary sinus floor augmentation as a preliminary pilot study. Five patients that required sinus floor augmentation to facilitate the placement of dental implants participated in this clinical study. The PRP was prepared from the autologous peripheral blood and was lyophilized and stored at −20 °C for 4 weeks before surgery. At surgery, triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[ 142 ] The use of autologous freeze‐drying platelet‐rich plasma (FD‐PRP) on bone regeneration in maxillary sinus floor augmentation has been mentioned in a preliminary pilot study. [ 143 ] The authors have noted that the results generated in this study suggest that autologous freeze‐drying platelet‐rich plasma can be used safely for bone engineering in clinical practice. It is also noted that FD‐PRP preserves platelet function, cytokine concentration, and functionality.…”
Section: Freeze‐dried Cellsmentioning
confidence: 94%
“…[ 142 ] The use of autologous freeze‐drying platelet‐rich plasma (FD‐PRP) on bone regeneration in maxillary sinus floor augmentation has been mentioned in a preliminary pilot study. [ 143 ] The authors have noted that the results generated in this study suggest that autologous freeze‐drying platelet‐rich plasma can be used safely for bone engineering in clinical practice. It is also noted that FD‐PRP preserves platelet function, cytokine concentration, and functionality.…”
Section: Freeze‐dried Cellsmentioning
confidence: 94%
“…The benefits of freeze-dried preparations are besides the prolonged viability of products, the possible storage in the refrigerator or at room temperature in its powder form which is optimal for mixing with other materials, such as the artificial bone. In a study by Koga et al (2021) the researchers evaluated the lyophilized form of PRP stored at -20°C for 4 weeks and discovered that the preparation remained safe to use in bone engineering up to 4 weeks after freeze-dried storage, with no side effects reported. Roffi et al (2014) reported that immediate and 7-day release of growth factors of frozen PRP was lower compared to the fresh preparation, but the cold stored preparation effectively preserved the ability to induce proliferation and extracellular matrix production, as shown in chondrocyte and synoviocyte culture.…”
Section: Musculoskeletalmentioning
confidence: 99%
“…Moreover, Li et al (2017) used 3D-printed biomaterial scaffolds for bone tissue engineering coated with freeze-dried PRP and showed significantly greater osteogenic differentiation induction compared to traditionally prepared PRP. Koga et al (2021) conducted a study with freeze-dried PRP stored at -20°C for 1 month, which was rehydrated and applied in five patients for sinus surgery mixed with bone grafting materials. The results were assessed 4 weeks after the surgery of maxillary sinus floor augmentation showing that the vertical augmented height was maintained and that the preparation remained safe to use in bone engineering up to 4 weeks after freeze-dried storage, with no side effects reported.…”
Section: Musculoskeletalmentioning
confidence: 99%
“…The maxillary sinus drains through its ostium into the nasal cavity, which usually takes place in the middle meatus. In around 25% of all maxillary sinuses, there is an accessory bone that is located lower than the main ostium, and all the mucus produced and the particles trapped in this mucus are directed through the ciliary beat to the ostium [3].…”
Section: Introductionmentioning
confidence: 99%